Expansion of Impervious Surface Area in Pekanbaru (1990–2018) and Predictions for 2038 Using Big Data - Wirawan Bayu Andrianto; Siregar Yusni Ikhwan; Sukendi Sukendi; Mulyadi Mulyadi (E3S Web of Conferences)
Climate change and biodiversity loss are two major ecological issues facing the world today, 25% of which are caused by land use change. The rate of development of the Pekanbaru City area has an impact on the phenomenon of Impervious Surface Area (ISA) growth that is inevitable in the suburbs. This situation can result in environmental degradation and unpreparedness of government officials so that the growth process leads to unsustainability. The development of spatial big data technology and high-performance cloud computing, the phenomenon of built-up land growth that occurs in Pekanbaru City can be studied further. By using programming carried out through the Google Earth Engine, the process of extracting the trend of built-up land growth in Pekanbaru City can be extracted quickly and presented in a multi-temporal. Through the polynomial regression modeling process with python, from the 1990-2018 data we can predict the area of built-up land in Pekanbaru City in 2038 is around 27985.139 hectares with r2 = 0.97. With accurate future predictions, we can take appropriate policies to handle urban growth sustainably.